LANGUAGE TESTING, EVALUATION AND FEEDBACK: IELTS PRIMARY TESTS - USMANOVA GULRUKH SHOKIRJONOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
In order to form the ability to read the original literature on the specialty, to participate in oral communication in a foreign language in the process of training future personnel in the system of higher education in the country and finding the necessary information for scientific purposes, English lessons wishing. An expert in his or her field should be able to read original English-language literature related to his or her profession, understand the text read, and apply it in his or her profession. In addition, he should be able to communicate freely in a foreign language with his interlocutor on a given topic. Therefore, a number of tests have been organized to determine the knowledge and skills of a foreign language. For instance, the Cambridge range of exams - FCE, CAE, CPE, as well as IELTS General, IELTS Academic, IELTS Life Skills, TOEFL and PTE and others. In this article, I would like to mention.